’Balance of Terror’ – Rival Militias and Vigilantes in Nigeria - Harnischfeger, Johannes (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Militias and vigilantes that assume public authority by fighting crime reject the laws of the state, yet they have no other set of rules to regulate their activities. Many of them claim to be accountable to their ethnic or religious community on whose behalf they operate. But their communities have found no means to institutionalise control over them. Moreover, there are no institutions to settle conflicts between different militias and vigilantes. On a local level, rival groups have reached informal arrangements. However, these compromises are unstable, as they reflect fragile alliances and shifting balances of power. Leaders of militias and other ’self-determination groups’ have suggested organising a conference of all ethnic nationalities in Nigeria in order to design a new constitution that would give militias and vigilantes a legal role and define their authority. But the groups compared in this article – Oodua People’s Congress, Sharia Vigilantes, Bakassi Boys, MASSOB, and Niger Delta militias – pursue very divergent interests, and they are far from reaching a consensus on how to contain violence between them.